2022
DOI: 10.1001/jamanetworkopen.2022.45818
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pack-Years of Cigarette Smoking With Survival and Tumor Progression Among Patients Treated With Chemoradiation for Head and Neck Cancer

Abstract: ImportanceAfter 10 pack-years of smoking was initially established as a threshold for risk stratification, subsequent clinical trials incorporated it to identify candidates for treatment deintensification. However, several recent studies were unable to validate this threshold externally, and the threshold for smoking exposure remains unclear.ObjectiveTo estimate the threshold of pack-years of smoking associated with survival and tumor recurrence among patients with head and neck cancer.Design, Setting, and Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…These findings underscore the importance of smoking cessation prior to initiation of RT for HNC. In addition to worsening OM risk, smoking during treatment has also been linked to worse survival . The contribution of chemotherapy to the development of severe OM remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings underscore the importance of smoking cessation prior to initiation of RT for HNC. In addition to worsening OM risk, smoking during treatment has also been linked to worse survival . The contribution of chemotherapy to the development of severe OM remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to worsening OM risk, smoking during treatment has also been linked to worse survival. 25 , 26 The contribution of chemotherapy to the development of severe OM remains unclear. While 2 studies 3 , 6 demonstrated concurrent chemotherapy to be associated with OM, our study and others 5 , 20 did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk categorization based on pack-years has been extensively adopted and continues to be used as a primary tool to identify patients at low risk appropriate for de-escalated therapy; however, emerging retrospective data from multiple groups would seem to indicate that tobacco exposure of 20–25 pack-years is a more accurate prognostic threshold [ 25 ]. Clinical trials have examined a variety of approaches for reducing therapy in HPV+ oropharynx cancer, with the use of chemotherapy to radically reduce radiation dose with a goal of diminishing late swallowing dysfunction, more modest reduction in radiation dose to reduce acute toxicity and duration of therapy, and transoral resection to permit pathology-driven treatment deintensification with the potential to spare chemotherapy and radiation.…”
Section: The Epidemic Of Hpv-associated Head and Neck Cancer And Tria...mentioning
confidence: 99%
“…Current evidence suggests that there is high variability in the clinical efficacy of different therapeutic modalities (Gavrielatou et al, 2020; Perrotti et al, 2021), however, clinicians lack predictive biomarkers to successfully correlate treatments with clinical response (Bouhaddou et al, 2021; Cohen et al, 2019; Gavrielatou et al, 2020; Ow et al, 2015). To date, smoking status (Ma et al, 2022), age (Stromberger et al, 2020) and HPV infection (Sabatini & Chiocca, 2020) have been shown to influence therapy outcomes in HNSCC. Additionally, mutations in the TP53 gene have been proposed as predictive biomarkers for therapy response, although inconsistent and controversial results have been reported (Basyuni et al, 2022; Ow et al, 2015).…”
Section: Introductionmentioning
confidence: 99%